Big five personality and citizenship performance of academics in a higher educational institution - Asmaa' Athirah Zulkifli (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
In the light of the growing interest in the literature of personality-citizenship performance link across jobs, the objective of this study was two-fold. Firstly, this study examines the relationship between the big five personality domains (i.e., openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) and citizenship performance of academics. Secondly, this study identifies which personality domain best predict citizenship performance of academics. Using a cross-sectional correlational survey design, a total number of 141 academics (Males = 67, Females = 73) from International Islamic University Malaysia have completed either an online survey or paper-based questionnaires. The questionnaires consist of Big Five Inventory and Citizenship performance scale by Hu, Jiang, and Li (2015). Results from the regression analyses have showed that: (1) openness to experience, conscientiousness, and extraversion are moderately and positively correlated with citizenship performance (r range from .47 to .49, p <.0005), (2) agreeableness is strongly and positively correlated with citizenship performance (r = .64, p <.0005), and (3) neuroticism is moderately and inversely correlated with citizenship performance (r = -.43, p <.0005). However, only agreeableness and openness to experience traits significantly predicted citizenship performance of academics (Oβ = .003, p<.0005; Aβ = .000, p<.0005). Accordingly, implications and limitations of this study are discussed and highlighted in order to provide recommendations for future research.